Restorative Justice for Corruptors in Indonesia; Why and How? - Ahmad Sahroni (Journal of Law, Society, and Islamic Civilization, 2024)
Corruption is always considered a major sin in Indonesia. In fact, it is not necessarily so. There need to be minimum requirements so that it can be said that corruption is indeed a major sin. For example, seen from the amount of corruption committed, there is good faith to return state money or not, to whether someone is the main perpetrator or not. Such things should be the basis for the implementation of restorative justice for corruptors. As a relatively new concept, the presence of restorative justice provides a breath of fresh air for the law enforcement system in Indonesia. Restorative justice strives to create conditions like before the crime occurred. Restorative justice can certainly realize qualified social welfare. Therefore, implementing restorative justice for corruptors is not something impossible. This study uses normative juridical research, with a legislative approach and a conceptual approach. The results of the research, corruptors should indeed be given the rights to be processed based on restorative justice. However, there are requirements that must be met, so that corruptors can be processed with restorative justice. In addition, this article also discusses how the concept of restorative justice is implemented in Indonesia.